(untitled) (Aporte Santiaguino, 2025)
This study assesses the use of mining tailings as fine aggregate in the production of low-strength concrete for sidewalk construction in a Peruvian mining area. The research responds to the urgent need for sustainable technical solutions to address the accumulation of environmental liabilities generated by mining activity. An applied, explanatory-level methodology was used, with a quantitative approach and quasi-experimental design. A total of 36 concrete specimens were produced, replacing natural fine aggregate with tailings at 0%, 10%, 25%, and 50%. The specimens were tested at 7, 14, and 28 days to evaluate compressive strength and workability. Results indicated that the 10% tailings mix achieved the highest compressive strength (248.50 kg/cm²) and demonstrated good cohesion, surpassing the control mix. These findings support the technical feasibility of incorporating tailings in non-structural infrastructure, promoting circular economy practices in mining-affected areas. Moreover, the controlled use of tailings may reduce dependence on natural resources and generate positive environmental and social impacts. The study contributes relevant scientific evidence for policies on mining waste reuse and sustainable construction practices, highlighting their applicability to urban infrastructure projects with low structural demands. The use of tailings in this context represents a viable and scalable strategy for improving environmental management and community well-being in mining regions.